2016
DOI: 10.1002/2015ja021729
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of heliospheric current sheet and stream interface: Implications for the origin and evolution of the solar wind

Abstract: In general, the heliospheric current sheet (HCS), which defines the boundary of sunward and antisunward magnetic field, is encased by the slow solar wind. The stream interface (SI) represents the boundary between the solar wind plasmas of different origin and/or characteristics. According to earlier studies using data of low time resolution, the SI and HCS get closer further away from the Sun, and the two structures coincide with each other around 5 AU. In this study, we use STEREO data of a much higher time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Besides the event presented in Huang et al . [], we found that some coincidence cases are related with ideal HCSs, namely, type (a) or (c), and some coincidence cases have a heat flux dropout (HFD) in the vicinity. Therefore, the coincidence cases are classified into three types.…”
Section: Observationsmentioning
confidence: 95%
See 4 more Smart Citations
“…Besides the event presented in Huang et al . [], we found that some coincidence cases are related with ideal HCSs, namely, type (a) or (c), and some coincidence cases have a heat flux dropout (HFD) in the vicinity. Therefore, the coincidence cases are classified into three types.…”
Section: Observationsmentioning
confidence: 95%
“…We will only show examples of type I and type III events in the following since a type II event is presented in detail in Huang et al . [].…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations